Culture of Openness on Women's Small-Scale Businesses in the Coastal Area of Medan - Ritha Fatimah Dalimunthe; Pujiati Pujiati (Universitas Medan Area, 2022)
This study was to figure out the effect of responsiveness to change, creativity, and ability to accept change on the competitive advantage of women’s small-scale businesses in the COVID-19 period in the coastal area of Medan. Respondents were women entrepreneurs in the coastal area of Medan with a total of 71 respondents. According to the data processing result on a questionnaire using multiple linear regression analysis, F-test, and also t-test, the study proved that variables of responsive to change, creativity, and ability to accept change simultaneously and significantly affected the competitive advantage for women’s small-scale business in the coastal area of Medan. Creativity significantly and partially affected the competitive advantage of women's small-scale businesses in the coastal area of Medan. Meanwhile, being responsive to change and the ability to accept change did not significantly affect the competitive advantage of women's small-scale businesses in the coastal area of Medan.